An assessment of the records management program of the Philippine Sports Commission - Unson, Dante Paolo V.; Buenrostro, Iyra S. (Quezon City Institute of Library and Information Science, University of the Philippines Diliman, 2002)
This study assessed the current records management program of the Philippine Sports Commission (PSC). The Commission, as the national government's primary funding arm for the development of sports in the country, is mandated by law to provide administrative services, such as records services. The records section and its records management program is the primary focus of this study. The study used the International Standard for Information Management ISO 15489-1:2001(E) as a basis for assessment. The study focused on the elements of a records management program: policy and guidelines, records management processes and controls, facility considerations and storage, and personnel training. The researcher used the descriptive method of research, thus conducting interviews and ocular inspection. The respondents for this particular study are the workforce of the records section, the records officer of the PSC and her staff.
Findings of the study describe the elements of the records management program currently employed in the Commission. Due to constant changes in senior management, issues in implementation of the organization's procedures on records arise. Findings of the study also showed certain gaps in certain records management processes of the PSC based on the International Standard regarding indexing and classification of records. The PSC lacks these two processes. Presently, the records section of the PSC is undergoing records appraisal and inventory to be able to formulate the records disposition schedule for the Commission.
From ocular inspection, the researcher found out that some of the facilities may be out-of-date. Some of the shelves have been utilized for more than a decade now, and would not seem to carry additional load. Also, the wooden shelves utilized by the PSC records section are not advisable for the storage of records because they are more susceptible to damage caused by insects, specifically termites. The training of personnel also needs to be updated since the last in-house training was conducted in 2003.
Recommendations include strict implementation of policy promulgated by the records officer, and because of the constant change in senior management, this set of guidelines should be flexible, should such changes occur. A records management program policy is proposed. Recommendations for procurement of new and stronger steel shelves were also suggested. Possible training schemes for records management personnel were also included in this paper.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Philippine Sport Commission; Records -- Management